Perbandingan Hasil Belajar Dengan Menggunakan Tes Teka Teki Silang (TTS) Dan Tes Pilihan Ganda Pada Materi Sistem Reproduksi Pada Kelas XI IPA SMAN 3 Lengayang Kabupaten Pesisir Selatan - Mardewita, Zulfi Dhani; Nurhadi, Nurhadi; Maizeli, Annika (STKIP PGRI Sumbar, 2014)
Â ABSTRACTÂ Â The background of this research is the lower result of student learning that obtained by the students. This cases caused of the daily examination that given is multiple choice, so many students do not understand the question because the students only guess the answer moreover, the students have less motivation in answer the question, because that is the common question for the students. In this case the student choose to be cheating the answer from the smart students. The researcher realize that problem, the researcher conducted the evaluation in crossword puzzle form. The purpose of the research is to known the result of learning in using crossword puzzle test and multiple choice test in Reproduction system material in biology learning. This research is experiment research. The population in this research is second grade of science class at SMAN 3 Lengayang in 2012/2013 academic year. This research is conducted in may 2013. The plan of this research is Randomized Control-Group Posttest Only Design. Based on the analysis that conducted, the average of class experiment I 83,58 and class experiment II 73,91. Hypothesis test using T test got the Thitung = 3,59 and Ttable =1,999 (real level 0,05), so the hypothesis received. From the data analysis thathave been obtained, In conclusion that the result of learning of biology students which use the crossword puzzle test better than the result of learning of biology students which use the Multiple choice in second grade of science class at SMAN3 Lengayang Regency of Pesisir Selatan.